Chronolibido and the problem of reading in Dying for Time. Issue 1 (2nd January 2016) - Yusin, Jennifer
Abstract : In his new book Dying For Time: Proust, Woolf, Nabokov, Martin Hägglund develops the notion of chronolibido, a new theory of desire that posits the constitutive difference of desire as testifying to temporal finitude and mortality as the object of desire. Rather than answering to the logic of lack, chronolibido offers a new model for reading literary and psychoanalytic texts as staging the drama of desire and temporal finitude. This essay takes up the problem of reading through an analysis of Hägglund's treatment of trauma in Dying for Time and argues that his notion of chronolibido becomes a literary trope for the philosophical concept of time as succession. In so arguing, I also aim to illuminate how Hägglund's deployment of the trope of desire in literary and psychoanalytic texts fosters a textual itinerary that problematically produces all such texts as the analogue of time as linear temporal succession while eliding the autonomy and agency of the signifying unconscious.